Effectiveness of a health technician-delivered brief intervention for alcohol: a Bayesian reanalysis of a clinical trial - Nicolas A. Barticevic; Fernando Poblete; Laura Bradshaw; Marcus Bendtsen (BMC Research Notes, 2022)
Abstract Objective To reanalyze a clinical trial on the effectiveness of a Brief Intervention (BI) delivered by non-professionals to reduce risky alcohol drinking. Our previous null-hypothesis test of the effects of the BI yielded a ‘non-significant’ p-value, yet remained uninformative. Here we use the Bayesian paradigm which allows for expressing the probability of different effect sizes to better inform public policy decisions. Results The posterior probability of the odds of risky drinking at follow-up favored a marked effect of the BI, with 96% of the probability mass being less than OR = 1, and 84% being less than OR = 0.8. Our findings show that there is a high probability that the BI delivered by health technicians lowered risky alcohol use. The posterior distributions of the BI’s effects are presented to help contextualize the evidence for policy making in Chile.